An Overview of Four-Leg Converters: Topologies, Modulations, Control and Applications - Espina-Gonzalez, E; Diaz-Diaz, M; Arancibia-Gonzalez, D (Institute of Electrical and Electronics Engineers Inc., 2022)
In three-phase unbalanced systems, where the circulation of zero sequence current is necessary, four-leg converters provide a neutral connection for single-phase or other unbalanced loads typically utilized in three-phase distribution systems. In addition, control of the magnitude and phase of the zero-sequence voltage and/or current are also achieved using four-leg power converters. However, even when four-leg converters have become very important in several fields as for instance, four-leg microgrids and aerospace applications, a comprehensive review of the converter topologies, control methods, modulation methods and output filters have not been hitherto published. In this paper, a comprehensive overview of the state-of-the-art of four-leg converters is presented, based on the selection of over 400 papers published in journals and conferences, identifying mature and incipient topologies, modulation strategies, control schemes and applications. Each topic presented in this work is thoroughly discussed and reviewed, analyzing characteristics, implementation issues, and reported advantages and disadvantages to provide a comprehensive overview of the current research and future challenges in four-leg converters. The most important applications of four-leg converters are also discussed in this work, including stand-alone power supply, uninterruptible power supplies, grid-connected 4-leg inverters, ground power units for aerospace applications, active filtering for power quality enhancement, cooperative control of 4-leg converters for micro-grid applications, among others. Finally, future work and conclusions are highlighted in this paper. © 2013 IEEE.